Railway engineer L.F. Nikolai: early period of life and work activity - Latysh, V. I. (History of science and technology, 2014)
The article highlights early period in the life and work activity of outstanding national railway engineer L. F. Nikolai (1844-1908). It is shown that Leopol’d Fedorovych Nikolai (Leopol’d-Fridrich Fridrihovych Nikolai) entered the history of national science and technology as an outstanding scientist in the field of building mechanics and hydraulics, as well as one of the founders of the national school on bridges construction. His early scientific achievements and participation in the first national railways construction are being highlighted in details.